2007
DOI: 10.1210/en.2007-0202
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Increases Tuberin Phosphorylation and Mammalian Target of Rapamycin Signaling through an Extracellular Signal-Regulated Kinase-Dependent Pathway in Rat Granulosa Cells

Abstract: FSH-mediated regulation of mammalian target of rapamycin (mTOR) signaling in proliferating granulosa cells and the effect of dihydrotestosterone (DHT) on this pathway were examined. Inhibiting mTOR activation using rapamycin significantly reduced the FSH-mediated increase in cyclin D2 mRNA expression, suggesting that mTOR plays a role in the FSH-mediated increase in granulosa cell proliferation. FSH treatment of granulosa cells showed a 2-fold increase in phosphorylation of p70S6 kinase (p70S6K), the downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 39 publications
7
52
1
1
Order By: Relevance
“…Previous studies from our laboratory have shown that 5␣-DHT inhibits FSH-mediated mitogenic signals in immature rat GCs leading to cell cycle arrest (6,31). Although the role of insulin as a regulator of growth and steroidogenesis in ovarian tissues is well documented, the undesirable consequences of insulin's stimulatory action have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have shown that 5␣-DHT inhibits FSH-mediated mitogenic signals in immature rat GCs leading to cell cycle arrest (6,31). Although the role of insulin as a regulator of growth and steroidogenesis in ovarian tissues is well documented, the undesirable consequences of insulin's stimulatory action have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway may therefore also be involved in the regulation of granulosa cell autophagy via control of mTOR activity during follicular development and atresia, as gonadotropin is known to suppress granulosa cell autophagy in follicular development (Choi et al 2010). However, there is also a report suggesting that mTOR activation by gonadotropin may not be controlled by the PI3K/AKT pathway in rat granulosa cells (Kayampilly & Menon 2007), and there is no direct evidence of the involvement of the PI3K/AKT pathway through mTOR in granulosa cell autophagy regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Chez la rate, la voie mTOR activĂ©e stimule la prolifĂ©-ration (induite par la FSH) des cellules de la granulosa [22] et celle des cellules de la thĂšque (induite par la LH) [23]. L'inhibition de mTORC1 dans des cultures primaires de cellules de la thĂšque induit une baisse d'expression des marqueurs de prolifĂ©ration, tels que PCNA (proliferating cell nuclear antigen) ou la cycline D3, et ce malgrĂ© l'induction de la prolifĂ©ration par de l'hCG (human chorionic gonadotropin) qui mime l'effet de la LH [23].…”
Section: Revuesunclassified